A Rare Case Of Solid Pseudopapillary Neoplasm (Spn) Of Pancreas In A Male Patient. (28th October 2020) - Arshi, J; Rao, D
Abstract: Introduction/Objective: SPN is a rare neoplasm of the pancreas with low malignant potential and unknown histologic origin. It has a strong preponderance in young females (Female:Male ratio = 9:1). Methods: We present a case of a 32-year-old morbidly obese male, who presented at our institution with an incidental large heterogeneous mass in the distal pancreas on imaging. Distal pancreatectomy with splenectomy was performed. Results: Grossly, the mass measured 8 centimeters in greatest dimension with a tan-brown variegated cut surface. The microscopic sections revealed a well-encapsulated tumor comprised of solid and cystic components. The solid areas show sheets and nests of hyalinized vascular stroma surrounded by small uniform cells with eosinophilic cytoplasm and bland round-to-ovoid nuclei. The immunohistochemical (IHC) stains showed variable positive expression with CD10, beta-catenin, and progesterone receptors. We also stained for newer putative IHC markers including LEF-1, TFE-3, SOX-11, and AMACR. Among them, LEF-1 was the only marker that showed 100% strong and diffuse, nuclear positive expression while the other three showed variable positive expression. These novel results are noted for the first time and is in congruence with the emerging molecular diagnostic finding that LEF-1 expresses the β-catenin binding domain of Wnt/β-catenin signaling pathway involved in the histologic origin of this tumor. Conclusion: We present a rare case of SPN in a male patient. Additionally, this is the first case to report the staining pattern of newer putative markers of LEF-1, TFE-3, SOX-11, and AMACR that may suggest the pathobiology of histologic origin of this tumor.